2011
DOI: 10.1128/iai.00785-10
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis-Host Interactions in aDrosophila melanogasterModel

Abstract: Porphyromonas gingivalis is a Gram-negative obligate anaerobe that has been implicated in the etiology of adult periodontitis. We recently introduced a Drosophila melanogaster killing model for examination of P. gingivalis-host interactions. In the current study, the Drosophila killing model was used to characterize the host response to P. gingivalis infection by identifying host components that play a role during infection. Drosophila immune response gene mutants were screened for altered susceptibility to ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 73 publications
2
21
1
1
Order By: Relevance
“…Our study, done using a defined isogenic mutant, shows that the nonencapsulated PgC strain is less virulent than the encapsulated W50 strain, thus demonstrating that indeed the capsule plays a role in the virulence of P. gingivalis in the mouse abscess model. These results are consistent not only with previous reports using the rodent abscess model but also with a recent publication demonstrating reduced virulence of the nonencapsulated PgC strain compared to that of encapsulated W50 bacteria in the fruit fly Drosophila melanogaster model of infection (26). A model of infection in which the outcome is bacterium initiated but host driven was used in the study, as is observed in the case of periodontal disease.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our study, done using a defined isogenic mutant, shows that the nonencapsulated PgC strain is less virulent than the encapsulated W50 strain, thus demonstrating that indeed the capsule plays a role in the virulence of P. gingivalis in the mouse abscess model. These results are consistent not only with previous reports using the rodent abscess model but also with a recent publication demonstrating reduced virulence of the nonencapsulated PgC strain compared to that of encapsulated W50 bacteria in the fruit fly Drosophila melanogaster model of infection (26). A model of infection in which the outcome is bacterium initiated but host driven was used in the study, as is observed in the case of periodontal disease.…”
Section: Discussionsupporting
confidence: 80%
“…The P. gingivalis capsule may also contribute to increased survival by reducing the bactericidal effect of defensins, small antimicrobial peptides produced by a variety of host cells. Indeed, a recent study demonstrated capsule-dependent increased resistance of P. gingivalis to defensins (26).…”
Section: Discussionmentioning
confidence: 99%
“…7). Finally, several immune response-defective Drosophila mutants show increased susceptibility to killing by P. gingivalis (36).…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-nine Drosophila flies per group were infected (as described above) with the following P. gingivalis strains: W83, ATCC 49417, 381, ATCC 33277, A7A1, and 23A4. Three animals per group were ground in 80 l of PBS with a Teflon pestle at the following time points (in hours) postinfection: 0, 4,8,12,24,36,48,60,72,84,96,108, and 120. Viable P. gingivalis cell counts were determined on BBA plates containing gentamicin (8 g/ml), amphotericin B (3 g/ml), and vancomycin (1 g/ml).…”
mentioning
confidence: 99%
“…Defensins, a small antimicrobial peptides produced by host cells have a bactericidal effect. P. gingivalis capsule reduces the bactericidal effect of these peptides contributing to increased survival of the organism (122). The non-encapsulated PgC strain is less virulent than the encapsulated W50 strain, demonstrating that capsule plays a role in the virulence of P. gingivalis in the mouse abscess model (111).…”
Section: Capsulementioning
confidence: 99%